2013
DOI: 10.1186/2228-5326-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on terahertz generation via laser interaction with a carbon nanotube array

Abstract: An amplitude-modulated laser, in the presence of a static magnetic field, interacts with an array of carbon nanotubes embedded on a metallic surface. The laser exerts a ponderomotive force on the free electrons of carbon nanotubes at twice the modulation frequency that falls in the terahertz (THz) range. Each nanotube acts as an oscillatory electric dipole, producing THz radiations. The presence of magnetic field shifts the resonance condition and provides tunability. The THz radiation power increases with mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The reason behind this observation is that, the applied magnetic field exerts force on the electrons of the medium and hence makes the interaction/system more nonlinear. The same observation was reported by Jain et al [20] where they have used a magnetized array of CNTs embedded on the metal surface to study radiation generation.…”
Section: Resultssupporting
confidence: 70%
“…The reason behind this observation is that, the applied magnetic field exerts force on the electrons of the medium and hence makes the interaction/system more nonlinear. The same observation was reported by Jain et al [20] where they have used a magnetized array of CNTs embedded on the metal surface to study radiation generation.…”
Section: Resultssupporting
confidence: 70%
“…and hence, the THz wave of maximum amplitude is by the system. Similar results were shown by Kumar et al [7] and Jain et al [21] where they applied the magnetic field on an array of CNTs embedded on the dielectric and metal surface respectively. It is also observed that at B = 75 kG, THz amplitude increases by 16% as compared to the THz amplitude in the absence of a magnetic field and attains peak value at the optimized value of the static magnetic field at B = 125 kG This is because the increase in the value of the static magnetic field increases the cyclotron frequency of the electrons of CNTs and hence, the nonlinear current density.…”
Section: Numerical and Graphical Analysissupporting
confidence: 83%
“…The band at 1090 cm −1 was attributed to the asymmetric stretching vibrations mode of phosphate groups [38], while the bands at 604 and 565 cm −1 were assigned to the bending vibration mode of phosphate groups [39,40]. The bands at 1038 and 451 cm −1 were assigned to the asymmetric and bending Si-O-Si stretching vibration of silicate groups, respectively [41,42]. The presence of Si-O-Si bending vibration which was attributed to normal vibration modes of Si-O in the SiO 4 group, indicated the presence of amorphous silicate [43].…”
Section: Resultsmentioning
confidence: 99%